(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to compare high sensitive Troponin T (hs-TnT), total antioxidant capacity (TAC), total oxidant capacity (TOC), oxidative stress index (OSI), ischemia-modified albumin (IMA) levels and IMA/albumin ratios (IMAR) with the results of coronary angiography (CAG) in patients diagnosed with ACS at the emergency department. Materials and Methods: Over a period of nine months, patients that were diagnosed with ACS at the emergency department, admitted to the cardiac intensive care unit, subjected to percutaneous CAG and over the age of 18 were included in the study. Results: One hundred twenty five patients with suspected ACS and 52 healthy volunteers were included in the study. When the patients were evaluated with regards to the length of time between symptoms and arrival, TAC levels were found to decrease especially after the 6 th hour. There was no significant difference between TOC, OSI, IMA and IMAR values in this regard. Conclusion: In early-phase ACS, levels of TOC, OSI, IMA and IMAR rise from the 0th hour onwards. TAC levels gradually decrease after the early phase of ischemia. Therefore, oxidants and antioxidants can be used for early diagnosis of ischemia in ACS, as well as for estimating time of ischemia onset.